Hand-coloured British Hydrographic Maps showing Goletas Channel to Quatsino Sound - Surveyor General of British Columbia (1864)
British Hydrographic Map surveyed by G.H. Richards, et al., 1860 and 1864. [Author of hand annotations of Indian Reserves not known, no date.] [Signed by G.M. Sproat, Indian Reserve Commissioner, "for dates see Decisions".]